Bainite ve Martensite Yapılarda Elektriksel Özdirenç - Aldırmaz, Emine (Fırat University, 2016)
Literatürde bazı bakır bazlı alaşımlarda, uygulanan ısıl işleme bağlı olarak martensite ve bainite yapılarının birlikte meydana geldiği gözlenmiştir. Martensite yapı ile bainite yapı yapısal olarak birbirine benzerlik gösterirken kristolografileri ve oluşum mekanizmaları birbirinden farklı özellikler göstermektedir. Yapılan bu çalışmada elektriksel özdirencin sıcaklıkla değişimi bainite ve martensite yapı için A.C. dört nokta kontak yöntemi kullanılarak ölçüldü. Bu ölçümler sonucunda martensite ve bainite fazın özdirençlerinin birbirinden farklılık gösterdiği bulunmuştur.

In literatüre, it was observed that the martensite and bainite structures occur simultaneously depending on heat treatment for some copper-based alloys. While martensite and bainite structures show structurally similarity, their crystallographand formation mechanism show different characteristics. In this study, the electrical resistivity as a function of temperature was measured using a standard four-point probe A.C. method for bainite and martensite structures. Result of these measuraments was shown that the electrical resistivity displays different results for martensite and bainite phases.
Electrical Resistivity in Bainite and Martensite Structures